Universal design guideline for public park recreational facilities / Mazzueen Md Khalid … [et al.] - Md Khalid, Mazzueen; A. Rahman, Azman; Mohd Sa’ad, Sri Rahayu; Ahmad, Che Bon; Sidek Malim, Ishak Malim (Research Innovation Business Unit, 2014)
In Malaysia,the disabled or orang kurang upaya (OKU) find it difficult to use recreation facilities in public parks due to lack of access and safety. The National Landscape Department and Universiti Teknologi MARA (UiTM) attempted to identify the accessibility for the disabled (OKU) visitors in public parks, to identify universal design criteria to meet the needs of the disabled in public parks and to provide universal design guidelines for public park recreational facilities. Universal design approach is to take into account with the specific needs and capabilities of users with unique needs as a solution of a complete design in public park environment that suitable and effective for all users, including the disabled. this universal design, need to meet the seven (7) basic principles and it must achieve an equal level of consumption; are flexible in terms of selection and the ability to use it; simple and easy to understand; providing information and informative; tolerance to danger or accident, the use of physical ability and the provision of a minimum size and user-friendly space. To establish the guidelines, as stated before, National Landscape Department collaborated with Universiti Teknologi MARA (UiTM) made an assessment of the disabled facilities in public parks. Several disabled associations and local authority were invited such as Persatuan Orang-orang Cacat Anggota Malaysia, Persatuan Orang Pekak Malaysia, Persatuan Bagi Orang Buta Malaysia and Persatuan Pengguna-penguna Standard Malaysia, Dewan Bandara Kuala Lumpur (DBKL), Majlis Bandaraya Petaling Jaya (MBPJ), Majlis Bandaraya Melaka Bersejarah (MBMB) and Jabatan Kebajikan Masyarakat (JKM). Series of workshops and consultation with these association and local authorities has been organized to get the input. The outcome of this research, a universal design guideline has been developed and published for use by local authorities for public benefit. In general, universal design in public park has been apply and acceptance by most of the countries in the world because to reduce the barrier and provide the facilities for the community. It gives the opportunity for the disabled to access the public park and participate in recreation activity. The application of universal design guideline in the development of public parks will give equal rights to all park users as a recreational area to socialize. Besides that this universal design handbook as a guide and reference to the parties involved in the planning and development of public parks. These guidelines have been published by National Landscape Department under Kementerian Perumahan dan Kerajaan Tempatan.